(untitled) (Proceeding of the International Conference on Arts and Humanities, 2020)
South Africa has undergone and continues to undergo dramatic changes on the educational landscape, particularly in higher education institutions (HEIs). The latest drive for decolonisation and Africanisation of the curriculum emanated from the 2015 student protests (#FeesMustFall; #RhodesMustFall). Decolonisation and Africanisation are not new concepts and are practices required to ensure that changes are carried out on curricula that are colonial and Eurocentric and which perpetuate Western bias. The research question deals with: What approaches need to be considered when developing strategies for editing of decolonised and Africanised texts in higher education in South Africa? The approach of this study is from an editing perspective with a qualitative, interpretive research paradigm. Although this study is cross-sectional, it forms part of a longitudinal study into understanding strategies and developing guidelines to decolonise and Africanise texts in HEIs in South Africa. Data for this study were collected from a literature review of editing strategies when decolonising and Africanising text. As there is a shortage of available literature in South Africa, editing practices for indigenous texts formed the unit of analysis for this study. In addition, empirical data were collected on the perceptions of educators in a South Africa HEI on, inter alia the extent and the process of decolonisation and Africanisation of the curricula. The findings of the study uncovered a number of editing strategies and themes that could be useful in developing a framework for the process of decolonisation and Africanisation of texts. Conclusions are provided and limitations for the study are delineated.